ALTERATION TO ARTICULATE OF THE SHOULDER HIP AND KNEE IN METHODSACTIVE, PASSIVE AND FNP IN HIDROGINÁSTICA PRACTITIONERS. (Fiep Bulletin - online, 2015)
The aging process is well-known that we live deeply in this period superior contemporary, indices to other times in the in agreement historia the ministry of the providence and social assistance (MOREIRA, 2001). The prognostic of loss of mobility to articulate of 20 30% between 30 the 70 years is alarming, (et.al DANTAS, 2002). The Importance of flexibility is not only limited in profit of the amplitude to articulate, it this directly related with domestic accidents and degenerative patologias..Entretanto is indispensable to know the alterations to articulate that the training of propitious flexibility. This research had as objective to verify the variations of the amplitude to articulate acute in the methods of training of flexibility, asset and facilitation to  neuromuscular proprioceptiva (FNP) inserted in the lesson of hidroginástica for practitioners of the feminine sex with total etária band between 40 and 74 agesNum of 16 enclosed participants the group of control.  Had  been applied techniques of descriptive statistics for characterization of the sample, and used protocol of Tran and Weltman (1989). For the dependent  variable it used ANOVA for the test of the hypotheses and determined the significant minimum difference. The angular percentile alterations in the methods and its respective joints value of F with level of significance 5%. The angular alteration of the joints in relation to the tested methods demonstrated resulted significant for method FNP having the lesser limitante factor of the alterations to articulate of the shoulder and hip, in the case of the knee this paper was played by the passive method. The study it demonstrated that when comparing applied methods we have resulted inversely satisfactory for the active method being thus a ontogênico stimulaton that did not increase mobility to articulate in the joints of the shoulder, knee and hip in short time in the sample.
Keywords: Methods of Flexibility; Alteration To articulate; idroginástica